Research in the heart of hematology: chronic myeloid leukemia 2017 - Hehlmann, Rüdiger (Haematologica, 2017)
One of the great success stories of modern hematology is reaching its next and possibly final phase: the achievement of treatment-free remissions in stable deep molecular responders with chronic myeloid leukemia (CML) which may well be equivalent to cure. Although only the minority of patients
Gesehen am 09.04.2018